2021
DOI: 10.1101/2021.11.19.21266466
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neoantigen DNA vaccines are safe, feasible, and capable of inducing neoantigen-specific immune responses in patients with triple negative breast cancer

Abstract: PURPOSECancer neoantigens are important targets of cancer immunotherapy. Neoantigen vaccines have the potential to induce or enhance highly specific antitumor immune responses with minimal risk of autoimmunity. We have developed a neoantigen DNA vaccine platform capable of efficiently presenting both HLA class I and II epitopes. To test the safety, feasibility and efficacy of this platform, we performed a phase 1 clinical trial in triple negative breast cancer patients with persistent disease following neoadju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
(53 reference statements)
1
2
0
Order By: Relevance
“…vaccinated with an average of 11 neoAgs per patient (42), confirming the feasibility of this approach.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…vaccinated with an average of 11 neoAgs per patient (42), confirming the feasibility of this approach.…”
Section: Discussionsupporting
confidence: 52%
“…Thus, our current results obtained in TNBC patients suggest that the TMB found may originate a sufficient number of neoAgs for vaccination. In fact, it has been recently reported the results of a phase I clinical trial of a neoAg-based DNA vaccine in 18 TNBC patients, where authors vaccinated with an average of 11 neoAgs per patient ( 42 ), confirming the feasibility of this approach.…”
Section: Discussionmentioning
confidence: 84%
“…We demonstrated that dual blockade of TIGIT and PD-1 can enhance the CD8 T cell response to neoantigen vaccines. Of note, neoantigen-specific CD4 T cells have been identified in several neoantigen vaccine studies ( 9 , 35 ) including our own neoantigen DNA vaccine trial in TNBC ( 38 ). Neoantigen-reactive CD4 T cells have also been shown to mediate clinical regression in a patient with cholangiocarcinoma when neoantigen-reactive CD4 T cells were adoptively transferred ( 39 ), further confirming the important contribution of neoantigen-specific CD4 T cells towards antitumor immunity.…”
Section: Discussionmentioning
confidence: 99%